Peran Pendidikan Jasmani dalam Pembentukan Karakter Peserta Didik - Kamaruddin, Ilham; Ridwan, Andi; Istiqamah, Nur; Saputri, Roswanda; A, Sitti Fatimah.; Kurniawan, Alif; H, Muh. Reyhan. F. (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Physical education plays a vital role in shaping students’ character through physical activities that foster moral, social, and emotional values. This article aims to examine the role of physical education in character formation, the character values that can be developed, and the supporting and inhibiting factors affecting its implementation in schools. This study employed a literature review method, analyzing books, scientific articles, and national and international journals relevant to the topic. The findings indicate that physical education significantly contributes to developing character values such as discipline, responsibility, cooperation, sportsmanship, honesty, empathy, and solidarity. The main supporting factors include the competence and moral example of physical education teachers, a positive school environment, the Merdeka Belajar curriculum, and adequate sports facilities. In contrast, the inhibiting factors consist of limited sports infrastructure, teachers’ focus on physical aspects over character formation, reduced instructional time, and the negative influence of digital technology on students’ social interaction. Therefore, physical education must be implemented in an integrated and reflective manner to ensure the continuous internalization of character values among students